Vibrotactile Perception for Sensorimotor Augmentation: Perceptual Discrimination of Vibrotactile Stimuli Induced by Low-Cost Eccentric Rotating Mass Motors at Different Body Locations in Young, Middle-Aged, and Older Adults - Pomplun, Ella; Thomas, Ashiya; Corrigan, Erin; Shah, Valay A.; Mrotek, Leigh A.; Scheidt, Robert A. (Frontiers in Rehabilitation Sciences, 2022)
Sensory augmentation technologies are being developed to convey useful supplemental sensory cues to people in comfortable, unobtrusive ways for the purpose of improving the ongoing control of volitional movement. Low-cost vibration motors are strong contenders for providing supplemental cues intended to substitute for proprioceptive sensations of limb posture and movement that may be lost or otherwise impaired due to neural injury or disease. However, it remains unclear what form such cues should take and where on the body they should be applied. One goal of this study is to use a low-cost, wearable technology to examine the acuity of vibrotactile stimulus intensity discrimination at several candidate stimulation sites on the body in a sample of participants spanning a wide age range. Another goal is to determine the extent to which the acuity of vibrotactile discrimination can improve over several days of discrimination training. Healthy adults performed a series of 2-alternative forced choice experiments that quantified capability to perceive small differences in the intensity of stimuli provided by low-cost eccentric rotating mass vibration motors fixed at various body locations. In one set of experiments, we found that older participants had poorer acuity of intensity discrimination than middle-aged and younger participants, and that stimuli applied to the torso were systematically harder to discriminate than stimuli applied to the forearm, knee, or shoulders, which all had similar acuities. In another set of experiments, we found that older adults could improve intensity discrimination over the course of three days of practice on that task such that their final performance did not differ significantly from that of younger adults. These findings may be useful for future development of wearable technologies intended to improve the control of movements through the application of supplemental vibrotactile cues.